Identification of large channels in cationic PEGylated cubosome nanoparticles by synchrotron radiation SAXS and Cryo-TEM imaging. Issue 18 (14th May 2015) - Angelov, Borislav; Angelova, Angelina; Drechsler, Markus; Garamus, Vasil M.; Mutafchieva, Rada; Lesieur, Sylviane
<x xml:space="preserve">Abstract</x> Liquid crystalline cationic cubosome nanoparticles with very large aqueous channels (Cryo-TEM image and the corresponding FFT pattern).